Taking advantage of online communities for generating innovative ideas - Robert Tietz; Cornelius Herstatt (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2005)
The use of the internet for business purposes and among consumers is spreading at an impressive rate. Companies use it for a lot of different activities like, for example, marketing, online shopping and customer service. However, the use of the internet for the purpose of innovation, to create ideas and concepts, is still underdeveloped. Practical experience shows that online communities are suitable for developing innovative ideas with users. To gain a deeper understanding of the underlying mechanisms we have taken a case-study approach. Based on this we generate a set of propositions concerning characteristics that a community should have in order to foster innovativeness. Our findings show that communities should be social, access should be restricted and it is necessary that users are free to post critical messages. Furthermore, the threads should be organised to create a lively discussion and users have to be able to build-up reputation.
urn:nbn:de:gbv:830-opus-1027
Keywords: 650; internet; online communities